What Do We Know About Rural Child Care? An Overview of Issues - Betty A. Beach (Journal of Research in Rural Education, 1995)
Although many contributions of preschool experiences to success in school have been documented, only limited understanding of this linkage exists for rural children. Most child care research has occurred in urban and suburban settings; by the standards developed through such research, rural children appear to face less available, lower quality care. They are also less likely to participate in the formal group programs considered by some observers to be important preparation for public school. This apparent disadvantage for rural children needs careful exploration, especially to (a) clarify the links between child care and public school transition; (b) understand better the patterns of child care choice and utilization among rural families; and (c) examine the ecological relationships among families, child care providers, schools and communities in the rural setting.